Pin-photodiode array for the measurement of fan-beam energy and air kerma distributions of X-ray CT scanners. Issue 7 (July 2016) - Haba, Tomonobu; Koyama, Shuji; Aoyama, Takahiko; Kinomura, Yutaka; Ida, Yoshihiro; Kobayashi, Masanao; Kameyama, Hiroshi; Tsutsumi, Yoshinori
Highlights: We devised a pin-photodiode array for the measurement of fan-beam energy and air kerma distributions of CT scanners. The pin-photodiode array consisted of eight channels of X-ray sensors. Fan-beam energy could be measured with the rotating exposure mode of CT scanners. Abstract: Purpose: Patient dose estimation in X-ray computed tomography (CT) is generally performed by Monte Carlo simulation of photon interactions within anthropomorphic or cylindrical phantoms. An accurate Monte Carlo simulation requires an understanding of the effects of the bow-tie filter equipped in a CT scanner, i.e. the change of X-ray energy and air kerma along the fan-beam arc of the CT scanner. To measure the effective energy and air kerma distributions, we devised a pin-photodiode array utilizing eight channels of X-ray sensors arranged at regular intervals along the fan-beam arc of the CT scanner. Methods: Each X-ray sensor consisted of two plate type of pin silicon photodiodes in tandem – front and rear photodiodes – and of a lead collimator, which only allowed X-rays to impinge vertically to the silicon surface of the photodiodes. The effective energy of the X-rays was calculated from the ratio of the output voltages of the photodiodes and the dose was calculated from the output voltage of the front photodiode using the energy and dose calibration curves respectively. Results: The pin-photodiode array allowed the calculation of X-ray effective energies and relative doses, at eight points simultaneously along the fan-beam arc of a CT scanner during a single rotation of the scanner. Conclusions: The fan-beam energy and air kerma distributions of CT scanners can be effectively measured using this pin-photodiode array.